Academic spin-offs in Finnish biotechnology: A portrait of firm characteristics - Antti-Jussi Tahvanainen (The Research Institute of the Finnish Economy (ETLA), 2004)
This paper portrays the characteristics of Finnish biotechnology SMEs that have their origin in academic research conducted in universities or other comparable research institutions. The portrayal facilitates the positioning of these firms within the sector as a whole and, even more importantly, enables the identification of strengths and weaknesses of academic biotechnology spin-offs as well as external factors that either promote or inhibit their prosperity from an entrepreneurial perspective. Leaning on results of a linear regression analysis based on a sample of 65 companies, it is found that academic biotechnology spin-offs are constraint in several ways. First, they lack a clear market-oriented focus as well as the commercial sense and skills to strategically direct their organization as a business towards the markets. Second, a very traditional and detached perception and definition of the academia's role and task within society – the concept of the “ivory tower” – makes it difficult for the companies to attract skilled labour. And last, Finland's equity markets are underdeveloped. New seed capital is next to unavailable, as private and foreign venture capitalists invest only in companies that are already very close to the markets. – – Tämä tutkimus kuvaa yliopistoissa tai vastaavissa tutkimusinstituutioissa tapahtuvaan akateemiseen tutkimukseen pohjautuvien pienten ja keskisuurten bioteknologiayritysten piirteitä. Kuvaus mahdollistaa yritysten asemoinnin suhteessa koko bioteknologia- alaan. Lisäksi kuvauksen pohjalta voidaan tunnistaa tutkimuksen kohteena olevien yritysten heikkouksia ja vahvuuksia sekä ulkopuoliset tekijät, jotka ovat yritysten kehityksen kannalta hyödyllisiä ja haitallisia. Tutkimuksessa käytetyn regressioanalyysin tulosten pohjalta voidaan todeta, että akateemiset spin-off-yritykset kärsivät monenlaisista rajoitteista. Ensiksikin heiltä puuttuu usein selkeä markkinaorientoitunut lähestymistapa sekä kaupallinen osaaminen, joita tarvitaan markkinoilla menestymiseen. Tämän lisäksi vallitseva käsitys, jonka mukaan akateemisten instituutioiden rooli ja yhteiskunnallinen tehtävä ovat perinteisiä ja kaupallisesta toiminnasta eristäytyneitä – metafora norsunluutornista – haittaa yritysten kykyä rekrytoida kyvykkäitä työntekijöitä. Ongelmaksi muodostuu myös Suomen pääomamarkkinoiden alikehittyneisyys tietyiltä osin. Tärkeää perustamisvaiheen rahoitusta on vaikea saada kun yksityiset ja ulkomaiset pääomasijoittajat sijoittavat pääasiallisesti yrityksiin, jotka ovat jo hyvin lähellä markkinoita.
Keywords: 330; Biotechnische Industrie; Biotechnische Forschung; Klein- und Mittelunternehmen; Betriebsaufspaltung; Finnland